Answer:
![(-17)/(21)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/oy4eqim40gxe1kij4u1nawbk75afctutaw.png)
Explanation:
Given: u and v be are the solutions of
Let
is the quadratic equation and u and v are the zeroes/solutions then
Sum of zeroes;
![u+v = (-b)/(a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7bah78jd1jcndym0ynp2hicn03nl0cqb18.png)
Product of zeroes;
![uv= (c)/(a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/d5vnqzs3xgzpe4kn1xey7lh51c5ox91s11.png)
Comparing
to
we get a= 3 , b= 5 and c = 7
![u+v = (-b)/(a) = (-5)/(3)----(i)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/u15n3n9z7bnqzq1cy8xr9laozddpvw577n.png)
![uv= (c)/(a) = (7)/(3)----(ii)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8enh63kif3obri64f8kffqvego6lwqizg7.png)
Now we have to find
adding and subtracting 2uv in numerator we get
![= (u^2+v^2+2uv-2uv)/(uv)= ((u+v)^2-2uv)/(uv)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rjrxu3lu44gg901kwtex85f78psml7jl2e.png)
Substituting the values from (i) and (ii) we get
![(((-5)/(3) )^2-2* (7)/(3) )/((7)/(3) ) = ((25)/(9) -(14)/(3) )/((7)/(3) )= ((25-42)/(9) )/((7)/(3)) =(-17)/(9) * (3)/(7) = (-17)/(21)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s8lxhq933yhgs8j6h8hexikxs8i50i4wqa.png)
Hence, the value of
is
![(-17)/(21)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/oy4eqim40gxe1kij4u1nawbk75afctutaw.png)